Дослідження кластерної структури часових рядів - Башкатов, Є. О. (ХНУРЕ, 2021)
These abstracts propose an algorithm for isolating the cluster structure in time series. This will allow to process samples of large volume, by reducing the dimensionality of the original sample for further effective statistical analysis in order to establish the properties of the original time series, such as fractality. The algorithm is universal for constructing dynamic visibility graphs of DVG for arbitrary time intervals of measurement reflection.
Keywords: часові ряди; кластер; алгоритм кластеризації; графа динамічної видимості